Analisis Kapabilitas Efektif guna Melaksanakan Operasi Militer dalam Kontra Insurjensi di Wilayah Papua - Mella, Stellar Nube; Cempaka Timur, Fauziah Gustarina; Widodo, Pujo (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2023)
Gray argues that a good strategy must be realistic and implementable by the available means. This study aims to analyze the capabilities needed to carry out military operations effectively to support the implementation of counterinsurgency. The research method used in writing this article is a qualitative research method with literature study which is carried out by collecting data by understanding and studying theories from various literature related to the research topic and then critically analyzing in order to answer research questions related to security force capabilities needed in the context of counterinsurgency, especially in the Papua region to support the implementation of the national defense strategy. The results of this study found that the capabilities needed include; Information Operations capabilities, intelligence capabilities, land and coastal (sea and air) border guarding capabilities, tactical air mobility to support movement, and troops with special capabilities in arresting/ enforcement of HVT (High Value Target). In addition, there are also institutional capabilities that need to exist i.e. civil governance or capabilities, institutional management capacity, harmonized command and control, logistics, and robust justice system and law enforcement.